A comparison of the neuropsychological profiles of people living in squalor without hoarding to those living in squalor associated with hoarding. (2nd December 2016) - Lee, Sook Meng; Lewis, Matthew; Leighton, Deborah; Harris, Ben; Long, Brian; Macfarlane, Stephen
Abstract : Objective: Squalor affects 1 in 1000 older people and is regarded as a secondary condition to other primary disorders such as dementia, intellectual impairment and alcohol abuse. Squalor frequently is associated with hoarding behaviour. We compared the neuropsychological profile of people living in squalor associated with hoarding to those presenting with squalor only. Methods: This study is a retrospective case series of hospital inpatient and community healthcare services of 69 people living in squalor (49 from aged care, 16 from aged psychiatry, 3 from acute medical and 1 from a memory clinic). Forty per cent had co‐morbid hoarding behaviours. The main outcomes were neuropsychologists' opinions of domain‐specific cognitive impairment. Results: The squalor–hoarding group ( M age 75.8, SD = 6.9, ) was significantly older ( p < 0.05) than the squalor‐only group ( M age 69.9 years, SD = 13.1), significantly more likely to have vascular or Alzheimer's type neurodegeneration ( p < 0.05) and significantly less likely to have alcohol‐related impairment ( p < 0.05). Chi‐square analyses revealed significantly greater rates of impairment for the squalor‐only group ( p < 0.05) in visuospatial reasoning, abstraction, planning, organisation, problem solving and mental flexibility, compared with the squalor–hoarding group. Logistic regression analysis indicated that impaired mental flexibility was a significant predictor and strongly indicated squalor only (odds ratio = 0.07; 95% confidence interval: 0.01–0.82). Conclusions: Preliminary evidence suggests that squalor associated with hoarding may have distinct neuropsychological features compared against squalor only. Future work should be conducted using a larger sample and a common neuropsychological battery to better understand the deficits associated with hoarding‐related squalor. Copyright © 2016 John Wiley & Sons, Ltd.